Demand uncertainty in skill-based competition - Sabrina Artinger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
How does demand uncertainty affect entry into skill-based competition? I investigate this question in a market entry experiment with skill-based payoffs by systematically varying two key elements of the market environment: demand risk and expected market size. Results show that people's reactions to demand risk depend on the market size: in small markets people enter more when demand is risky, in large markets they enter less when demand is risky. This leads to substantial inefficiencies in both cases: demand risk significantly amplifies overentry in small markets and underentry in large markets. Skill and confidence have strong main effects but do not moderate reactions to demand risk or market size. This result has important implications for market design and regulation.
Keywords: D03; D80; D23; 330